DESIGNING AND VALIDATING ONLINE COURSE EVALUATION INDICATORS: INSIGHTS FROM LEARNER ENGAGEMENT AND EXPERT REVIEW IN THE CHINESE CONTEXT - Zhang, Zhijun; Abdullah, Nabilah; Abdul Aziz, Norazah; Wu, Qinghao (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Online learning has become a part of higher education in most parts of the world, but most existing models of evaluation are primarily influenced by Western thinking and thus fail to represent the multicultural environment that many global learning centres embody. Since the fast development of online higher education in China has introduced the acute necessity to introduce credible and context-specific assessment systems that would precondition the quality and efficiency of digital learning settings, despite all the international frameworks, some of them do not consider the pedagogical, cultural, and policy contexts of Chinese universities. This research suggests a theoretical model of the online course assessment indicators design and validation in the Chinese college environment. Based on the learner engagement theory and expert review methodology, the framework incorporates three main steps: the first step is to consider the possible indicators based on the global and national literature; the second step available is the refinement and validation of the indicators based on expert consultation using the established content validity techniques; and finally, a plan of empirical testing among the Chinese learners is outlined. The proposed model focuses on the combination of all three dimensions of behavioural, emotional and cognitive engagement to provide quality evaluation that is learner-centred. The study can be used to build a localised and theoretically grounded instrument to enhance the quality assurance of online education in China.